Women in society: Israel - Uval, Beth (Singapore : Times Books International, 1993)
Examines the experiences of women in Israeli society, discussing their participation in various fields and profiling the lives of significant women.
Includes bibliographical references (p. 127) and index.
Keywords: Women -- Israel -- Social conditions -- Juvenile literature